Caracterização bioquímica e avaliação da atividade antifúngica de lectinas de sementes de Fabaceae da Amazônia - (:unkn) unknown (Universidade Federal do Amazonas, 2012)
Seeds of 50 Amazonian species of Fabaceae with individuals of the subfamilies Caesalpinioideae, Mimosoideae and Faboideae were analyzed for the presence of new lectins. The total extracts were tested for hemagglutinating activity (AHE). The protein xvi extracts of Anadenanthera peregrina, Dimorphandra caudata, Ormosia lignivalvis, Dioclea bicolor and the protein fractions of Swartzia laevicarpa exhibited AHE with rabbit erythrocytes, and this activity was inhibited by galactose or lactose, but not by glucose or mannose. The total extract of Swartzia laevicarpa exhibited AHE only after submitted to an ion exchange chromatography and their lectin were purified by affinity chromatography with immobilized lactose. Even with the large number of lectins reported in leguminous plants, this is the first description of lectins in the genera Anadenanthera, Dimorphandra and Ormosia. The study of lectins from these geners and from Swartzia gender may contribute to the understanding of the evolutionary relationships of legume lectins, in terms of their structure properties and their proteic processing. The lectins from species of the subtribe Diocleinae are known to be specific to glucose and mannose, but the protein extract from the seed of the species Dioclea bicolor exhibited AHE with rabbit erythrocytes and this activity was inhibited by galactose and lactose. After the Dioclea bicolor seed lectin (DBL) was purified on an affinity resin with immobilized lactose. The sequencing of internal peptides of DBL showed homology with leguminous lectins belonging to groups Dalbergieae, Phaseoleae, Sophoreae. The Swartzia laevicarpa seed lectin (SLL) agglutinated rabbit erythrocytes, but did not for mouse erythrocytes. The lectin activity remained after heating at 100 °C for 15 minutes and was strongly inhibited by N - acetyl - D - galactosamine, α - lactose and D - galactose. The SLL exhibited an electrophoretic pattern constituted by a single proteic band corresponding to an apparent molecular mass of 29 kDa, which was confirmed by spectrometric mass analysis and still the SLL reacted positively with Schiff reagent. The amino acid sequence (39 amino acids) from N-terminal region and the internal peptides sequence was determined by Edman degradation and MS/MS, respectively. The SLL sequencing showed complete homology with the legume lectins belonging to the most primitive groups (Dalbergieae and Sophoreae). The SLL (1 mg / mL) did not exhibited antifungal activity against the five phytopathogens tested
Keywords: Purificação; Proteínas e carboidratos; Purification; Proteins and carbohydrates; CIÊNCIAS BIOLÓGICAS